Estrés laboral y su incidencia en la salud mental de un trabajador de 40 años, del Municipio en el cantón Montalvo - Verdezoto Gaibor, Jordy Bryan (2022)
In this case study it is evident how stress in the workplace can cause affectation in the mental health of a 40-year-old worker of the municipality in the canton Montalvo, after the individual has gone through different situations that have acted as pressures at the emotional level and that little by little have been manifested at the somatic level, has been analyzed through the different evaluation instruments such as the Clinical History, Clinical Observation, also psychometric evaluation instruments such as; the Beck Depression test, the Beck Anxiety test and the Maslach Burnout Inventory which have helped to find certain symptoms in the cognitive, affective, social and somatic areas, which agree with the patient's problems; Cognitive Behavioral Therapy techniques have also been used the same ones that have been worked on throughout the sessions, and have been sent as tasks to home, all this accompanied by a qualitative methodology; and with the help of the International Classification of Diseases CIE-10 it has been possible to determine the presumptive diagnosis in the patient.